A mother's touch a study on the impact of maternal education on the educational outcomes of their children - Magpantay, Isaac Raphael C.
This study aims to study the impact of maternal education on the probability that children will achieve higher educational outcomes. An ordered probit model was used, and marginal effects were computed in order to assess the effect of maternal education on the probability of achieving higher educational outcomes. The results suggest that parental education has a significantly positive effect on the probability that a child will achieve higher levels of education, with maternal education having a stronger effect. Aside from this, results also suggest that daughters are more likely to attain higher educational outcomes regardless of parental education and urbanity. Lastly, household income is also statistically significant, with higher levels of income associated with higher likelihood of higher education. The results of this study point towards policies targeted towards improving the low educational attainment of mothers and daughters, given how the benefits of maternal education lasts across generations.